Trend Research on STEM Learning Trough Bibliometric Mapping Analysis: Contribution to Science Education Undergraduate Program - Fatimah, Siti; Chamdani, Muhammad; Syahidi, Khaerus; Mahmudah, Umi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This study aims to analyze the trend of STEM research publications in undergraduate education each year, visualize the trend of STEM research in undergraduate education, and how STEM research contributes to undergraduate science education. This study was conducted in September 2023 using bibliometric analysis. This study uses the following search terms in the title, abstract, and keywords: "STEM Learning" AND "undergraduate". The researcher only considered scientific articles published each year and did not limit the publication source. The initial data analysis resulted in 116 documents, then there were 109 documents that were relevant to the search criteria. The documents were analyzed using VOSViewer and Biblioshiny. The data was documented in (.csv) format. Next, this data was processed and analyzed using the VOSViewer and Biblioshiny applications to analyze the trend of research on STEM in undergraduate education programs.